1990
DOI: 10.1055/s-2006-960919
|View full text |Cite
|
Sign up to set email alerts
|

Batch Cultures of Somatic Embryos ofDigitalis lanatain Gaslift Fermenters. Development and Cardenolide Accumulation

Abstract: Somatic embryos of DIGITALIS LANATA STRAIN VII were successfully grown as batch cultures in gaslift fermenters. Embryo development and formation of cardenolides in the embryos resembled those of cultures grown in shake flasks. Both processes depended on the developmental stage of the embryos at the time point of inoculation, the homogeneity of the embryo structures, the density of the inoculum, the composition of the nutrient medium, the intensity of irradiation, and the composition of the gas mixtures used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
0
8
0
1
Order By: Relevance
“…Stuhlemmer et al [6,60] and Greidziak et al [6,61] reported the formation of about 1 mg cardenolides/g dry weight in partly submerged shoot cultures and somatic embryoids, respectively. In a more recent study, salicylic acid, exogenous yeast polysaccharides, and calcium chloride were tested for their capacity to enhance cardenolide formation in D. lanata shoot cultures.…”
Section: Biology and Physiologymentioning
confidence: 99%
“…Stuhlemmer et al [6,60] and Greidziak et al [6,61] reported the formation of about 1 mg cardenolides/g dry weight in partly submerged shoot cultures and somatic embryoids, respectively. In a more recent study, salicylic acid, exogenous yeast polysaccharides, and calcium chloride were tested for their capacity to enhance cardenolide formation in D. lanata shoot cultures.…”
Section: Biology and Physiologymentioning
confidence: 99%
“…The large scale production of plants using bioreactors employing liquid medium can be achieved through induction of somatic embryogenesis, as in Digitalis lanata (Greidziak et al 1990), or by using shoot meristem multiplication technique as in Digitalis purpurea (Hagimori et al 1984) and in Stevia rebundiana (Akita et al 1994). Some other important medicinal plants propagated in bioreactors include: Atropa belladonna, Asparagus officinalis, Artemisa annua, Acanthopanax koreanum, Chlorophytum borivilianum, Digitalis lanata and Brahmi (Mehrotra et al 2007;Praveen 2009;Haque et al 2009;Rizvi and Kukreja 2014).…”
Section: Production Of Secondary Metabolites Of Maps From Cellmentioning
confidence: 99%
“…Some examples of this effect are the synthesis of tropane alkaloids in roots differentiated from callus of Atropa belladonna,lo the production of morphinane alkaloids during somatic embryogenesis of Papaver somniferum, II the synthesis of indole alkaloids in root and shoot cultures of C. roseus,12 the synthesis of the flavonoid naringin in shoot cultures of Citrus paradisi, 13 and the accumulation of cardenolides in somatic embryos of Digitalis lanata. 14 The expression of secondary metabolic pathways in redifferentiated cell cultures is actually not surprising because it mimics exactly what the plant does. Furthermore, in most cases the synthesis of plant natural products is under strict temporal and spatial control.…”
Section: Introductionmentioning
confidence: 99%